Education, skills and citizenship: an emergent model for entrepreneurship in Tanzania - DeJaeghere, Joan (Comparative education, 2013)
Educating for citizenship is most often associated with a discourse of liberalism in which knowledge, skills and values of equality, rights, justice and national identity are taught. A competing neoliberal discourse with values of self-improvement, responsibility and entrepreneurialism is now quite pervasive in educational policies and practices, shifting goals and processes of education for citizenship. In Tanzania, neoliberalism's influence is evident in the private provision of schooling and pedagogy and curriculum oriented toward skills development. Neoliberal policies have created an opening for non-governmental organisations (NGOs) to fill a need by providing secondary education as well as technical and entrepreneurial skills in efforts to make graduates more employable. This paper examines how an NGO entrepreneurship education programme integrated into formal secondary education in Tanzania articulates new goals and values of citizenship. In this model, learning is tied to markets; becoming a successful citizen includes acquiring business skills; and citizenship values include economic sustainability and self-reliance. This model of entrepreneurship education produces a paradox in educational goals for citizenship in that it aims to secure rights to education and provide for material needs while it also subjects young people and schools to economic and social risks tied to flexible and unstable markets.